Sistem Pendukung Keputusan Pembelian Rumah Menggunakan Metode Fuzzy dan Metode Simple Multi Attribute Rating Technique (Smart) - Taufik Kurnialensya (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Home is one of the primary needs of society. Various considerations of a person in buying a house, including considerations in terms of accessibility, environmental safety, road infrastructure and drainage, price, size and layout, building structure and model, availability of internet connection and signal layout, building structure and model, availability of internet connection and cell phone signal, availability of water and electricity, legal availability of water and electricity, legality, distance to workplace, and public facilities.public facilities. The fuzzy method is able to be used to classify the set of membership criteria and the SMART method can be used to rank the value of the criteria used criteria used. Calculations that have been carried out starts from using a fuzzy method that is useful for finding the set of membership criteria, followed by calculating the membership set of criteria, followed by calculating the matrix and ranking with the SMART method. ranking with the SMART method. Ranking with the highest value is house 2 with a value of 87.16 followed by house 3 with a value of 85.87 followed by house 1 with a value of 84.92 and the last house 4 with a value of 72.13